2016
DOI: 10.1097/bcr.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Regional Anesthesia for Pediatric Burn Reconstructive Surgery

Abstract: Pediatric patients face multiple reconstructive surgeries to re-establish function and aesthetics post burn injury. Often, the site of the harvested graft for these reconstructions is reported to be the most painful part of the procedure and a common reason for deferring these reconstructive procedures. This study in pediatric burn patients undergoing reconstructive procedures examined the analgesia response to local anesthetic infiltration versus either a single ultrasound guided regional nerve block of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Shank et al compared surgical site infiltration (0.25% bupivacaine), ultrasound-guided single-shot lateral femoral cutaneous nerve block, and ultrasound-guided continuous infusion fasciailiaca compartment block on postoperative pain in children undergoing reconstructive skin grafting. 47 The authors reported that patients who received regional anesthesia via single-shot lateral femoral cutaneous nerve block (LFCNB) or catheter infusion fascia iliaca compartment block (FICB) experienced less pain than those in the surgical site infiltration group. The patients in the LFCNB group reported significantly less postoperative pain upon arrival to the post-anesthesia care unit until discharge to the floor compared with the FICB group or the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Shank et al compared surgical site infiltration (0.25% bupivacaine), ultrasound-guided single-shot lateral femoral cutaneous nerve block, and ultrasound-guided continuous infusion fasciailiaca compartment block on postoperative pain in children undergoing reconstructive skin grafting. 47 The authors reported that patients who received regional anesthesia via single-shot lateral femoral cutaneous nerve block (LFCNB) or catheter infusion fascia iliaca compartment block (FICB) experienced less pain than those in the surgical site infiltration group. The patients in the LFCNB group reported significantly less postoperative pain upon arrival to the post-anesthesia care unit until discharge to the floor compared with the FICB group or the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Regional anesthesia in its simplest form may be tumescent local anesthesia injected into a donor site prior to harvesting 75 or it can take the form of subcutaneous catheter infusions, 76 peripheral nerve, or central neuraxial blocks. 77 …”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Sometimes there is a need to cover the anterior and medial thigh due to the extent of skin harvest, and therefore a fascia iliaca block can also be performed. [76][77][78] …”
Section: Regional Anesthesiamentioning
confidence: 99%
“…Regional anesthesia in its simplest form may be tumescent local anesthesia injected into a donor site prior to harvesting 75 or it can take the form of subcutaneous catheter infusions, 76 peripheral nerve, or central neuraxial blocks. 77 Central neuraxial techniques (spinals, epidurals) have been utilized with good effect as both primary anesthetics and postoperative adjuncts in burn injured patients. There are no reports suggesting epidural abscesses are more common in burn patients, but reports have suggested that intravascular catheters are more likely to become infected if placed in or near burned tissue; 78 similarly caution is likely reasonable in selecting appropriate burn patients for central neuraxial techniques.…”
Section: Regional Anesthesiamentioning
confidence: 99%